Different response rate to interferon in cgronic hepatitis B: importance of precore mutant and serum ferritin level - Yusuf BAYRAKTAR,; Tankut KÖSEOĞLU,; Aytekin TEMİZER,; Gürol ÖKSÜZOĞLU,; Durrişehver ÖZER,; Bedri UZUNALİMOĞLU,; Burhan KAYHAN, (Turkish Journal of Gastroenterology, 2019)
-